Evaluasi Kepatuhan Minum Obat Pada Pasien Pengidap Hiperkolesterolemia Di Puskesmas Kota Selatan - Saputro, Prio Adi; Abdulkadir, Widy Susanti; Manno, Mohamad Reski; Taupik, Muhammad; Anggai, Rifka Anggraini (-, 2026)
Hypercholesterolemia is a condition in which blood cholesterol levels exceed the normal range, representing a major public health concern. This condition is closely associated with cardiovascular diseases, which, according to the WHO (2018), are the leading cause of death worldwide. The increasing prevalence of high cholesterol in Indonesia is influenced by changes in diet and lifestyle. Medication adherence plays a crucial role in achieving therapeutic success and optimal health outcomes. This study aimed to determine the level of medication adherence among patients with hypercholesterolemia at Kota Selatan Public Health Center (Puskesmas). The study employed a quantitative descriptive design using a survey method. The population consisted of 61 patients, with 31 respondents selected as the sample. The instrument used was the Morisky Medication Adherence Scale-8 (MMAS-8), and the data were analyzed using univariate analysis. The results showed that the level of medication adherence among patients was moderate, with 17 respondents (54,83%) categorized as adherent and 14 respondents (45,17%) as non-adherent. The highest adherence was observed among patients aged 24-44 years (100%), males (75%), those with a diploma or bachelor's education (86%), and those undergoing treatment for less than one year (67%). Overall, the level of medication adherence among patients with hypercholesterolemia at Kota Selatan Public Health Center was classified as moderate. Increased education and patient support are recommended, particularly for older adults, women, and those with education levels, to enhance treatmentt success.